Assessment of Secondary School Science Students’ Digital Citizenship - Razzaq Ahmad, Sheikh Tariq Mehmood, Tariq Javed, (JSE, 2023)
This study was planned to assess how secondary school science students are aware of digital citizenship and its nine components. Major objectives of the present study were; to assess the knowledge of digital access, digital communication, and digital etiquette among secondary school science students, to explore the skills of digital law, digital literacy, and digital commerce among secondary school science students, and to assess the awareness of digital safety and security, digital rights and responsibilities, and digital wellness among secondary school science students.